Agreement between the United Kingdom of Great Britain and Northern Ireland and the Swiss Confederation on the Extension of the Temporary Agreement between the United Kingdom of Great Britain and Northern Ireland and the Swiss Confederation on Services Mobility done at London on 14 December 2020, London, 14 and 17 November 2022. ([2023-01-20]) - Unknown
No abstract available